The Curriculum School Based on International Standart - Syarif, Fajar (Ali Muchasan, 2019)
This research represents curriculum at International Standard School. This research is interesting to be carried out because the curriculum in International Standard School is still survived and it is widely adopted by many educational institutions. This research is written by studying many documentation resources being described in books, journals, and so on. First, the researcher describes the substance of International Standard School and then the curriculum that is implemented in the International Standard Schools. The description shows that the curriculum in International Standard School has big role in educating students. The research finally shows that curriculum is one of important factor to attain success as well as a certain educational failure.